2003
DOI: 10.2134/jeq2003.4800
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate Leaching and Nitrogen Recovery Following Application of Polyolefin‐Coated Urea to Potato

Abstract: High N fertilizer and irrigation amounts applied to potato (Solanum tuberosum L.) on coarse-textured soils often result in nitrate (NO3) leaching and low recovery of applied fertilizer N. This 3-yr study compared the effects of two rates (140 and 280 kg N ha(-1)) of a single polyolefin-coated urea (PCU) application versus split applications of urea on 'Russet Burbank' potato yield and on NO3 leaching and N recovery efficiency (RE) on a loamy sand. Standard irrigation was applied in all years and excessive irri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
99
3
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 150 publications
(126 citation statements)
references
References 27 publications
20
99
3
1
Order By: Relevance
“…In the current study, greater yield response at the low N rate by banding a mixture of UAN and NF compared with UAN at Concord may be attributed to reduced surface runoff and leaching losses due to high early-season precipitation after N application (Table 1). Zvomuya et al (2003) found that values of NO 3 -N leaching with polymercoated urea ranged from 7 to 62 kg ha −1 , which was 34 to 49% lower than urea.…”
Section: Yield Traits and Harvest Indexmentioning
confidence: 92%
“…In the current study, greater yield response at the low N rate by banding a mixture of UAN and NF compared with UAN at Concord may be attributed to reduced surface runoff and leaching losses due to high early-season precipitation after N application (Table 1). Zvomuya et al (2003) found that values of NO 3 -N leaching with polymercoated urea ranged from 7 to 62 kg ha −1 , which was 34 to 49% lower than urea.…”
Section: Yield Traits and Harvest Indexmentioning
confidence: 92%
“…Potatoes have a relatively high cost of production and value, with average expenditures of $1780 to $2690/acre (55). Nearly 20% of operating cost is fertilizer, and potatoes require more than most crops (47,49,57,91). The combination of high fertilizer rates and acreage makes nutrient management an important priority in potato production.…”
Section: Nutrient Management In Potatomentioning
confidence: 99%
“…The consequence of poor efficiency and high water/fertilizer rates in potato is the potential for significant N contamination to surface (23,24,47,49) and groundwater (22,24,41,47,48,49,60,86,91). In addition, nitrous oxide emissions from potato fields are higher than those of most other crops (61,62), which is likely related partially to high fertilizer and water application rates (49).…”
Section: Nutrient Management In Potatomentioning
confidence: 99%
“…The use of specialized "controlled-release" N fertilizer sources, including PCU and urea amended with IU, has the potential to minimize NO 3 -leaching (Wilson et al, 2010;Zvomuya et al, 2003) and nitrous oxide emissions (Halvorson et al, 2010;Hyatt et al, 2010). There is some concern, however, about the effectiveness of PCU and IU under dryland conditions because of erratic release rates with fluctuating soil moisture (Fujinuma et al, 2009) and studies showing limited or no effectiveness (Sistani et al, 2011;Venterea et al, 2011).…”
Section: Core Ideasmentioning
confidence: 99%